Evaluasi Lapis Pondasi Agregat Kelas A (LPA) Dengan Menggunakan Metode Sand Cone - Defa Febriana; Muh Handy Dwi Adityawan; Fitriah Fitriah (Jurusan Teknik Sipil, Universitas Halu Oleo, 2024)
The sand cone test is a density test to determine the density sub-base or base-course aggregate foundation layers in the Project field. The purpose of this study is to determine the density value of base-course aggregate foundation layer in the Preservasi Jalan Wolo - Batas Kota Kolaka II project. The research method used is a quantitative method by conducting tests in the field and compared from laboratory test results. From the results of laboratory tests, the maximum density in the field is 2.23 gr/cm³, with the optimum moisture content value is 5.84%. The results of field testing from 20 points, the lowest density is 100.02%, thus all points meet the specifications of SNI 1743: 2008, method D.